Prevalence of simian malaria parasites in macaques of Singapore - Li, Irene Meizhi (2021)
Plasmodium knowlesi is a simian malaria parasite currently recognized as the fifth causative agent of human malaria. Recently, naturally acquired P. cynomolgi infection in humans was also detected in Southeast Asia. The main reservoir of both parasites is the long-tailed and pig-tailed macaques, which are indigenous in this region. Due to increased urbanization and changes in land use, there has been greater proximity and interaction between the long-tailed macaques and the general population in Singapore. As such, this study aims to determine the prevalence of simian malaria parasites in local macaques to assess the risk of zoonosis to the general human population. Screening for the presence of malaria parasites was conducted on blood samples from 660 peridomestic macaques collected between Jan 2008 and Mar 2017, and 379 wild macaques collected between Mar 2009 and Mar 2017, using a Pan-Plasmodium-genus specific PCR. Positive samples were then screened using a simian Plasmodium species-specific nested PCR assay to identify the species of parasites (P. knowlesi, P. coatneyi, P. fieldi, P. cynomolgi, and P. inui) present. All the peridomestic macaques sampled were tested negative for malaria, while 80.5% of the 379 wild macaques were infected. All five simian Plasmodium species were detected; P. cynomolgi being the most prevalent (71.5%), followed by P. knowlesi (47.5%), P. inui (42.0%), P. fieldi (32.5%), and P. coatneyi (28.5%). Co-infection with multiple species of Plasmodium parasites was also observed. The study revealed that Singapore's wild long-tailed macaques are natural hosts of the five simian malaria parasite species, while no malaria was detected in all peridomestic macaques tested. Therefore, the risk of simian malaria transmission to the general human population is concluded to be low. However, this can be better demonstrated with the incrimination of the vectors of simian malaria parasites in Singapore.